A green approach to encapsulate proteins and enzymes within crystalline lanthanide-based Tb and Gd MOFs - Tocco, Davide; Joshi, Madhura; Mastrangelo, Rosangela; Fratini, Emiliano; Salis, Andrea; Hartmann, Martin (Dalton Transactions, 2024)
In this work, bovine serum albumin (BSA) and Aspergillus sp. laccase (LC) were encapsulated in situ within two lanthanide-based MOFs (TbBTC and GdBTC) through a green one-pot synthesis (almost neutral aqueous solution, T = 25 °C, and atmospheric pressure) in about 1 h. Pristine MOFs and protein-encapsulated MOFs were characterized through wide angle X-ray scattering, scanning electron microscopy, thermogravimetric analysis, Fourier transform infrared and Raman spectroscopies. The location of immobilized BSA molecules, used as a model protein, was investigated through small angle X-ray scattering. BSA occurs both on the inner and on the outer surface of the MOFs. LC@TbBTC, and LC@GdBTC samples were also characterized in terms of specific activity, kinetic parameters, and storage stability both in water and acetate buffer. The specific activity of LC@TbBTC was almost twice that of LC@GdBTC (10.8 μmol min−1 mg−1vs. 6.6 μmol min−1 mg−1). Both biocatalysts showed similar storage stabilities retaining ∼60% of their initial activity after 7 days and ∼20% after 21 days. LC@TbBTC dispersed in acetate buffer exhibited a higher storage stability than LC@GdBTC. Additionally, terbium-based MOFs showed interesting luminescent properties. Together, these findings suggest that TbBTC and GdBTC are promising supports for the in situ immobilization of proteins and enzymes.
CRIS-Team Scopus Importer:2024-08-02